Active colloids in harmonic optical potentials(a)Contribution to the Focus Issue Statistical Physics of Self-Propelled Colloids edited by Hartmut Löwen, Sabine Klapp and Holger Stark. (1st October 2022) - Buttinoni, I.; Caprini, L.; Alvarez, L.; Schwarzendahl, F. J.; Löwen, H.
Abstract: We study the motion of active Janus colloids in an optical trap using experiments, theory and numerical simulations. To achieve isotropic and harmonic confinement, we prototype microparticles with a nearly uniform refractive index and verify that, in the absence of activity, the confined motion is identical to that of optically homogeneous Brownian particles. If the activity is turned on by means of vertical AC fields, the density distributions are described by Boltzmann-like statistics (Gaussian with effective temperature) only for strongly confining traps, whereas weaker potentials give rise to non-Gaussian distributions with a bimodal shape. Our results showcase a simple way to study active soft matter in optical potential landscapes eliminating the optical torque.